Indium oxide-a transparent, wide-band gap semiconductor for (opto)electronic applications - Bierwagen, Oliver (Semiconductor science and technology, 2015)
The present review takes a semiconductor physics perspective to summarize the state-of-the art of In2O3 in relation to applications. After discussing conventional and novel applications, the crystal structure, synthesis of single-crystalline material, band-structure and optical transparency are briefly introduced before focussing on the charge carrier transport properties. The issues of unintentional n-type conductivity and its likely causes, the surface electron accumulation, and the lack of p-type conductivity will be presented. Intentional doping will be demonstrated to control the electron concentration and resistivity over a wide range, but is also subject to compensation. The control of the surface accumulation in relation to Schottky and ohmic contacts will be demonstrated. In the context of scattering mechanisms, the electron mobility and its limits will be discussed. Finally, the Seebeck coefficient and its significance will be shown, and ferromagnetic doping of In2O3 will be critically discussed. With this overview most if not all ingredients for the use of In2O3 as semiconductor material in novel or improved conventional devices will be given.